KPI - METHODS AND TECHNIQUES USED FOR ACCOUNTING INSIDE ERP SAP- A STUDY CASE - Viorel – Costin Banta (Annals of the University of Craiova: Economic Sciences Series, 2018)
Inside companies, the ERP solutions have been adopted in order to help manage their work, to have integrated solutions with clear targets, and to have a comprehensive visibility of existing processes. In our case, ERP adopted solution SAP it has been implemented with a clear scope: all our processes should be managed together, all results obtained from this system, should be accessible to all interested persons. Our research, for this paper, was oriented to Key Performance Indicators (KPI) established for an economic entity, for daily, weekly, monthly, quarterly, yearly-performed work within an accounting department. We want to offer a perspective, for interested people, showing how they can manage their activities, making use of applying formulas established in our research. This developed solution – the ZKPI application, was adapted in SAP, using ABAP as a programming language, more than that, WebDynpro was the technology used. The ZKPI module/application was integrated with our core SAP system and is maintained by internal developers. In order to monitor the entire activity performed by accountant colleagues for Treasury and Tax department. We want to highlight that a part of our data was automatically collected (most of it) and some of data were manually introduced into the system (based on Excel files, text delimited, etc.). This tool it used inside a big oil and gas company. This paper aims to facilitate the understanding of the KPI implementation into the ERP system, the constraints in terms of processes in this area - oil and gas - and will provide guidelines from lessons learned in this regard